Influences of Parenting Style on Independence and Confidence Characteristics of Pre-School Children - Yuliani, Fitri; Awalya, Awalya; Suminar, Tri (Journal of Primary Education)
This study aims to analyze the differences in independence and confidence character of preschool children (4-5 years) based on parenting style. This study used a quantitative approach. The population of this study was the parents of 4-5-year-old children of Early Childhood Education Programs (PAUD) Gugus Nusa Indah Candisari Sub-district Semarang. The sampling technique used proportionate stratified random sampling, and the calculation of sampling amount used Slovin's Formula to collect 112 respondents. The data collecting method used a questionnaire with a Likert scale as the measurement scale. The data analysis technique used ANOVA test to analyze the difference between independence and confidence based on parenting style. The results of the study showed that from the ANOVA test, the probability value (pvalue = 0.000). Thus, it was found that there was a difference in pre-school (4-5 years old) children’s independence and confidence level based on the parenting style. There was a difference in children’s independence level based on the parenting style, the comparison of independence scale and parenting style was found that the value of the mean difference (MD) = 12.16 with the significance level of 0.000 < 0.05. There was a difference in children’s confidence level based on the parenting style, the comparison of independence scale and parenting style was found that the value of the mean difference (MD) = 18.5 with the significance level of 0.000 < 0.05. The conclusion of this study is that there was a positive and significant difference in children’s independence level based on the parenting style. There was a positive and significant difference in children’s confidence level based on the parenting style.